간호사의 건강문제에 따른 프리젠티즘과 결근율의 관계 - 이영미(Young Mi Lee); 정문희(Moon Hee Jung) (지역사회간호학회지, 2008)
Purpose: The purpose of this study was to examine the presenteeism and absenteeism in relation to the health problems of nurses. Method: Informed consent was provided before study. Data was collected from January 7 to March 6, 2008 by Stanford Presenteeism Scale-13. Data was collected from 3 hospitals in Seoul Gyeonggi area. The response rate of the questionnaires was 96.2%. Incomplete data was analyzed using SPSS program. Results: Shoulder, back and neck pain were the highest reported health problems and primary health Problem of nurses. Impaired presenteeism was ranked in this order: depression or anxiety, cold, and uterus or ovary disorder. Absenteeism was ranked in this order: uterus or ovary disorder, cold, and dermatological problem. Impaired presenteeism was significantly increasing according to the number of health problems. But Absenteeism was not. Presenteeism was significantly different by age, educational level, religion, whether or not the worker lived with their family, marital status, whether or not the worker has children, time spent in the workforce, experience of turnover, shift work, night work, and level of satisfaction with salary. But absenteeism was not significantly different given these criteria. Conclusions: Health problems of nurses can negatively effect the quality of nursing service and productivity at hospital. Therefore the hospital administrator should control the presenteeism and absenteeism through the management of health problems of nurses.